SIMULASI NUMERIK KEGAGALAN BALOK BAJA ALUMUNIUM BERLUBANG MENGGUNAKAN SKEMA THREE-POINT LOADING - Prabowo, Andy; Ie, Michelle Karen Julia (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2024)
The aluminium steel structures have relatively long term durability, high strength-to-weight ratio, and corrosion resistance. Investigations on the strength and performance of aluminium structures, both as a structural beam and column, can be found in various existing literature. However, studies that investigate the behaviour and strength of aluminium beams with a web hole remain scarce to date, even though the hole can accommodate building utility lines going through a structural element. This research aims to study the behaviour and strength of perforated aluminium beams using finite element modelling to simulate failure due to a three-point loading scheme. The finite element (FE) model in this study employed two approaches: full-section modelling and half-section modelling, which were then compared to the referred experimental test results. In total, 14 test specimens were built in the FE models, where the failure modes as well as the moment versus curvature curves obtained from the FE models, were quite similar to the test results. Furthermore, failure loads obtained from the test and FE models were very close, with the mean of test-to-FE loads was 0.97 and the coefficient of variation (COV) of 0.038 at maximum. It demonstrates that the numerical model developed in this study is valuable for further parametric study of the aluminium perforated beam, which fails under a three-point loading scheme.